Analysis of etiology and clinical features of spontaneous downbeat nystagmus: a retrospective study - Zhang, Sai; Lang, Yilin; Wang, Wenting; Wu, Yuexia; Yan, Shuangmei; Zhang, Ting; Li, Dong; Liu, Shaona; Hao, Yongci; Yang, Xu; Gu, Ping (Frontiers in Neurology, 2024)
Objective To investigate the topical diagnosis, possible etiology and mechanism of spontaneous downbeat nystagmus (sDBN) patients with dizziness/vertigo. Methods The clinical features of dizziness/vertigo patients accompanied with DBN were retrospectively reviewed in the Vertigo Center of our hospital from January 2018 to March 2021. The clinical features of dizziness/vertigo patients accompanied with DBN were reviewed. Comprehensive VNG, bithermal caloric testing, video-head-impulse test (vHIT), vestibular-evoked myogenic potentials (VEMP), head magnetic resonance imaging (MRI), three-dimensional fluid-attenuated incersion recovery magnetic resonance imaging (3D-FLAIR MRI) in the inner ear, serum immunology and other examinations were to determine the lesion site, and analyze its possible etiology and mechanism. Results A total of 54 patients were included. Among them, 70.4% (n = 38) of DBN patients were diagnosed with episodic vestibular syndrome (EVS), 22.2% (n = 12) with chronic vestibular syndrome (CVS), and 7.4% (n = 4) with acute vestibular syndrome (AVS). Among all the patients, 51.9% of DBN patients had clear etiology, with central lesions of 29.6% and peripheral diseases of 22.2%. The most common diseases in DBN patients were cerebellar lesions (13.0%, n = 7) and vestibular migraine (13.0%, n = 7), followed by benign positional paroxysmal vertigo (7.4%, n = 4) and drug-related dizziness/vertigo (5.6%, n = 3). The other 48.1% of the patients had unknown etiology. 53.8% (14/26) of patients with idiopathic DBN had decreased semicircular canal function, with 42.9% (6/14) decreased posterior semicircular canal function. The posterior semicircular canal gain in DBN patients decreased compared to the anterior semicircular canal in the same conjugate plane. Patients with peripheral DBN were more prone to horizontal/torsional nystagmus during positional testing. Conclusion In our study, DBN patients have a relative decrease in posterior semicircular canal gain, which is possibly a particular result found in a subset of downbeat nystagmus patients. The changes in nystagmus during positional testing may be helpful in distinguishing between peripheral and central causes.